DEMISTIFIKOVANI ZAKON: O ZABRANI VELA, KANCELPARAGRAFU I MILITANTNOM SEKULARIZMU U SOCIJALISTIČKOJ JUGOSLAVIJI - Božić, Marko D (Pravni zapisi, 2021)
Despite being closely examined from the perspective of its political background, the 1950 Yugoslav burka ban as a legal text remained until now beyond interests of historians of law. Exposing this Yugoslav law to a strictly normative analysis and comparison with analogous contemporary bans, this paper delivers the findings that largely exceeded the results of historical studies done so far. Though a brief text, the Yugoslav burka ban was a composite legislation that surely contained full-face veil ban, but also penalized criminal acts against unveiling and introduced an embryo to the future socialist Kanzelparagraph i.e., pulpit law as well. Openly aiming to break a religiously inspired behavior, its militant advocacy was only apparently distinct from a more neutral wording of the present-day veil-bans. A thorough analysis of its ideological foundation, however, indicates a crucial common feature with the modern laical legislation: the paternalistic state action excluding religion as such from the open public space and free debate. As such, the legacy of the Yugoslav socialist burka ban contributes to better understanding of militant secularism as surely a modern, but not a new controversy.
Keywords: Burka Ban; Kanzelparagraph; socialist Yugoslavia; socialist secularism; militant secularism